Analisis Proses Kegiatan Manajemen Sarana Prasarana Di Smp N 1 Percut Sei Tuan - Pandiangan, Errason; Sinurat, Ester; Manik, Lolona; Simbolon, Krisna Natalin; Yuniastuty , Eni (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Educational facilities and educational infrastructure are not the same. Educational facilities are all facilities (equipment, supplies, materials, and furniture) that are directly used in the teaching and learning process, both movable and immovable, so that the achievement of educational goals can run smoothly, orderly, effectively, and efficiently, such as buildings, classrooms, chairs, and learning media tools, libraries, school offices, student council rooms, parking lots, and laboratory rooms. This study aims to determine the process of management activities in the field of facilities and infrastructure at SMP Negeri 1 Percut Sei Tuan and the suitability of the process of management activities for facilities and infrastructure at SMP Negeri 1 Percut Sei Tuan. The results of the study indicate that the management of facilities and infrastructure at SMP Negeri 1 Percut Sei Tuan includes planning, utilization, inventory, maintenance, and disposal. Planning is carried out based on a needs analysis to support learning. Facilities are utilized optimally until they can no longer be used. Inventory is carried out in an orderly manner to facilitate supervision and maintenance. Maintenance is carried out routinely by school staff, while disposal is carried out according to procedures for efficiency and workload reduction. In general, management has been running well, although there are still infrastructure limitations that need to be improved.